East to West to South to North—and Back: Driving Landscapes as a Thuringian Long-Distance Trucker. Issue 1 (1st March 2022) - Moser, Manuel
Abstract: In this article, I map out landscaping practices by Thuringian long-distance truck drivers. Drawing on extended fieldwork, I show that contemporary truck drivers who drive the German and European highways with their political (and often racist) ideas in tow, structure their landscapes according to the four cardinal points. While getting disillusioned by experiences of an unwelcoming West that loses its utopic shine it had during the times of the German separation, Thuringian drivers strongly refuse to subsume themselves into a European East, which they "orientalize" as dangerous and barbaric. I argue that as a solution to this lived tension between East/West, Thuringian truckers increasingly relocate utopic places into the European North and South while intermingling geographies with ideologies, drawing especially from popular country music.